Patagonia-Antarctica Early Paleozoic conjugate margins: Cambrian synsedimentary silicic magmatism, U-Pb dating of K-bentonites, and related volcanogenic rocks - González, Pablo Diego (2018)
Fil: Gonzalez, Pablo Diego. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina.